EXPLORING THE BIODEGRADATION POTENTIAL OF CRUDE EXTRACELLULAR ENZYME MIXTURE FROM ANOXYBACILLUS SP. FOR AZO DYE REMOVAL: A SUSTAINABLE APPROACH FOR INDUSTRIAL WASTEWATER TREATMENT - Nirmalya Pal, Mitun Chakraborty, (Chelonian Research Foundation, 2023)
Urbanization, globalization, and industrialization have resulted in the accumulation of environmental contaminants such as organic chemicals, metals, and dyes. The textile industry is a significant contributor to environmental contamination due to the emission of wastewater containing harmful reactive and azo dyes, which are known mutagens, carcinogens, and teratogens. Several microorganisms, including bacteria, algae, fungi, and yeasts, can effectively degrade industrial dyes; however, their efficacy significantly depends on their adaptability and activity. This study investigated the potential of crude extracellular enzyme preparation from thermophilic indigenously isolated Anoxybacillus sp. in the biodegradation of azo dyes at high temperatures. This could be an innovative method for treating wastewater contaminated with azo dyes, including RB5, Methyl Orange, and Congo Red. The crude enzyme was isolated from Anoxybacillus sp. and its effect was investigated in vitro at a pH and temperature range of 4-8 and 20-60°C, respectively. The residual concentrations of selected dyes were measured using a UV-Vis spectrophotometer. The results demonstrated that the Anoxybacillus sp. crude enzyme effectively decolorized the azo dyes, indicating its potential for industrial applications. Additionally, the crude enzyme retained its decolorization capacity even at high temperatures and low pH. The highest decolorization occurred at 60℃ for all three dyes and a pH of 4.This study provides a basis for the large-scale production and application of extracellular, thermostable, crude enzyme mixtures using a low-cost substrate. The dye-decolorization efficiency of this bacterial isolate makes it an environment-friendly, low-cost, and effective option for industrial use. Keywords: Azo dyes, Crude extracellular enzyme, Decolorization, Anoxybacillus sp., Thermophile